Pediatric Collagenous Gastroenteritis and Colitis Presenting as Protein-Losing Enteropathy. Issue 4 (10th April 2023) - Remien, Kailey A.; Mancuso, Marisa; Watson, Kevin
ABSTRACT: There is a lack of literature on pediatric collagenous colitis. This is a report of a child with collagenous gastroenteritis and colitis who presented with chronic, nonbloody diarrhea and lower extremity edema secondary to protein-losing enteropathy. Collagenous colitis is rare in children; collagenous gastroenteritis and colitis are even less documented; and this diagnosis does not typically present with protein-losing enteropathy. The pediatric patient in this report had a presentation of a rare disease. Her disease self-resolved, and she has remained asymptomatic without pharmacologic intervention. This illness should be considered in a child presenting with this constellation of symptoms.